Cryo-EM Structures of the Human Endolysosomal TRPML3 Channel in Three Distinct States - Zhou, Xiaoyuan (Nat Struct Mol Biol, 2017)
TRPML3 channels are mainly localized to endolysosomes and play a critical role in the endocytic pathway. Their dysfunction causes deafness and pigmentation defects in mice. TRPML3 activity is inhibited by low endolysosomal pH. Here we present cryoelectron microscopy structures of human TRPML3 in the closed, agonist-activated, and low-pH-inhibited states, with resolutions of 4.06, 3.62 and 4.65 Å, respectively. The agonist ML-SA1 lodges between S5 and S6 and opens an S6 gate. A polycystin-mucolipin domain (PMD) forms a luminal cap. S1 extends into this cap, forming a ‘gating rod’ that connects directly to a luminal pore-loop, which undergoes dramatic conformational changes in response to low luminal pH. S2 extends intracellularly and interacts with several intracellular regions to form a ‘gating knob’. These unique structural features, combined with electrophysiological studies, reveal a new mechanism thereby luminal pH and other physiological modulators such as PIP(2) regulate TRPML3 by changing S1 and S2 conformations.